Informasi Mengenai Perempuan dalam Berita di Kompas.com Female - Kamila, Rizka Awalia; Laksmi, Laksmi (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2017)
This thesis discusses information about women who were found in a news at one news portal online kompas.com. In this thesis, researchers only focus on a canal is namely kompas.com female. Researchers trying to analyze the contents of information on women in some news in kompas.com female canal in a period of and assoociated with the concept of patriarchal culture that can represent existence of women. The purpose of this research is to identify how information about women pertaining to patriarchal culture on the news in kompas.com female canal. This research used the quantitive approach with the contents analysis method. The conclusion of this thesis shows that there is a contradiction between information about women on news with the concept of patriarchal culture. Contradiction referred to are women make news at online media as a source of their inspiration in develop itself to live and work on their demand without any restriction and interdiction. It was obtained from news as presented in the period April in kompas.com female canal. This period chosen because in it there are special topic of news namely ”Kartini-Kartini Masa Kini” who researchers assume as representative of women nowadays.